2016
DOI: 10.4338/aci-2016-06-r-0105
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap

Abstract: SummaryObjective: Decisions made during electronic health record (EHR) implementations profoundly affect usability and safety. This study aims to identify gaps between the current literature and key stakeholders' perceptions of usability and safety practices and the challenges encountered during the implementation of EHRs. Materials and Methods: Two approaches were used: a literature review and interviews with key stakeholders. We performed a systematic review of the literature to identify usability and safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…The governance of the EHR implementation 13 , 19 , 37 , as well as leaders 7 , 10 , 36 , 44 , 48 , [52] , [53] , [54] , 62 , 63 and organizational culture, were identified as paramount in ensuring a successful EHR system 7 , 10 , 13 , 36 , 45 , [50] , [51] , [52] , [53] , 56 , 59 , 62 . Whilst top-down, middle-out and bottom-up governance structures have been utilised, ongoing political willingness, national policies and some independence at an individual organizational level regarding EHR procurement, development and design, were recommended to promote engagement, usability and interoperability 13 , 48 , 51 , 62 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The governance of the EHR implementation 13 , 19 , 37 , as well as leaders 7 , 10 , 36 , 44 , 48 , [52] , [53] , [54] , 62 , 63 and organizational culture, were identified as paramount in ensuring a successful EHR system 7 , 10 , 13 , 36 , 45 , [50] , [51] , [52] , [53] , 56 , 59 , 62 . Whilst top-down, middle-out and bottom-up governance structures have been utilised, ongoing political willingness, national policies and some independence at an individual organizational level regarding EHR procurement, development and design, were recommended to promote engagement, usability and interoperability 13 , 48 , 51 , 62 .…”
Section: Resultsmentioning
confidence: 99%
“…An initial exploratory scope of the EHR literature in the PubMed database was reviewed by the expert panel and the final research question, methodology and search strategy were developed and agreed. A large number of search terms to describe “Electronic Health Record”, “Implementation” and “ Literature Review” were identified from previous systematic reviews 7 , [36] , [37] , [38] , [39] , [40] , additional literature 17 , medical subject heading and controlled vocabulary and via consultation with the expert panel and an experienced information technologist at the Health Sciences Library, UCD [Appendix]. The search string was tailored to the indexing language of each database and in March 2019, it was executed across PubMed, CINAHL, Scopus, Embase, Web of Science, IEEE Xplore, ACM Digital Library, ProQuest and Cochrane, with limitations of English language and published since 2010.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of these core components is strengthened by performance review meetings that unify multiple health system levels (provincial, district, facility, and community) to assess data quality, highlight areas of weakness, and plan improvements. Other studies have demonstrated that with adequate financial and human resources, implementation of EMR systems can accelerate and systematize data feedback loops to core stakeholders, such as is the case in Rwanda [ 33 ]. In the three PHIT projects involved in this study, intervention components that aligned with user priorities and government systems were perceived to be relatively advantageous, and more readily adapted and adopted, which will facilitate efforts to sustain and spread data quality improvements.…”
Section: Discussionmentioning
confidence: 99%
“…As a major research target in the field of HCI, usability refers to how useful, usable, and satisfying a system is for the intended users to accomplish goals in the work domain by performing certain sequences of tasks [9]. TURF, as one of the major and mainstream methods for usability evaluation, is a theoretical framework that assesses the usability of EHRs from three dimensions, including usefulness, usability, and user satisfaction [9–11].…”
Section: Introductionmentioning
confidence: 99%
“…TURF, as one of the major and mainstream methods for usability evaluation, is a theoretical framework that assesses the usability of EHRs from three dimensions, including usefulness, usability, and user satisfaction [9–11]. According to the definitions of TURF, the usability evaluation of eHealth products is divided into degree of inherent complexity (usefulness) and degree of exogenous complexity (usability and satisfaction) [10, 11].…”
Section: Introductionmentioning
confidence: 99%